Rationale and protocol for a longitudinal cohort study of children with cerebral palsy in China assessing functional developmental trends, genetic aetiology and imaging - Jing Zhang; Jinhua Lu; Wenhao Zhou; Yuan Zhang; Hongyu Zhou; Fan Wu; Ting Gao; Jie Luo; Jinling Li; Jingbo Zhang; Lu He; Tingting Peng; et al. (BMJ Open, 2025)
Introduction Cerebral palsy (CP), the most common physical disability in children, imposes substantial economic and psychological burdens on families and society. The clinical management of CP remains challenging due to the limited efficacy of current treatments and the heterogeneity of its aetiologies and clinical presentations. This study aims to investigate the functional changes and identify influencing factors in Chinese children with CP. Through analysis of neuroimaging and genetic data, this study seeks to inform the development of preventive and therapeutic strategies and guide healthcare decision-making for this population.Methods and analysis This prospective cohort study aims to recruit 2051 children with CP across China. Baseline data will include demographic and clinical characteristics. Participants will undergo comprehensive assessments, including motor, cognitive, language, social, behavioural, nutritional, pain, sleep and quality-of-life domains, with regular follow-up evaluations. Trio whole-exome sequencing and detailed neuroimaging and musculoskeletal imaging will also be performed. This study will also assess caregivers’ quality of life and emotional burden. Mendelian randomisation will be adopted to evaluate genetic contributions to functional outcomes and their causal relationship with health metrics. Analytical methods will include correlation analysis, logistic regression (binary and multivariate), linear and non-linear mixed-effects models and structural equation modelling.Ethics and dissemination Ethics approval was granted by the Research Ethics Committee of Guangzhou Women and Children’s Medical Center (No.2023-346A01). All study procedures will adhere to the approved protocol. Study findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration number ChiCTR2300079017.